CORRELATION BETWEEN LEFT VENTRICULAR CONTRACTILITY AND MYOCARDIAL T1-RELAXATION TIME DURING MAPPING IN PATIENTS WITH HYPERTROPHIC CARDIOMYOPATHY BY MAGNETIC RESONANCE IMAGING - O. Yu. Dariy; S. A. Aleksandrova; V. S. Bereznitskiy; L. A. Yurpol’skaya; V. N. Makarenko; L. A. Bockeria (Вестник рентгенологии и радиологии)
Objective. To determine a correlation of myocardial deformation with myocardial T1-relaxation time during extracellular volume (ECV) fraction mapping and the degree of focal fibrosis in each left ventricular (LV) segment in patients with hypertrophic cardiomyopathy (HCM). Material and methods. A diagnostic test was carried out in 30 patients diagnosed with HCM and in a control group of 10 patients without LV pathology. Cardiac magnetic resonance imaging was performed on a 3.0 T Philips Achieva TX MRI scanner (Philips, Best, the Netherlands) in accordance of the specialized protocol using a 32-channel cardiac coil with heart rate synchronization and the use of gadolinium-based contrast agents at a dose of 0.3 ml/kg. LV T1 mapping was done using the Modified Look-Locker Inversion Recovery (MOLLI) sequences. Postprocessing was performed on Philips and CVI42 workstations. When the data were processed, T1-relaxation time was estimated before and after contrast enhancement.Results. In all cases, myocardial thickness, extent of myocardial fibrosis, myocardial T1-relaxation time parameters, and ECV could be estimated according to the American Heart Association 16-segment coronary artery model. Before injection of contrast agent, the average LV T1 relaxation time in patients with HCM was 1317±94 msec which was significantly higher than that in the control group (1093±23.7 msec). ECV in the control group was lower (24.8±1.9%) than that in the HCM group (29.8±4.5%). In the univariable group, each index was related to myocardial deformation indicators (radial (Err-FT) and circular (Ecc-FT)) at the segment level. There was a moderate positive correlation between LV thickness and Ecc-FT (r=0.52; p<0.0001), a moderate negative correlation between Err-FT and LV hypertrophy (r=–0.5; p<0.0001), and between Err-FT and myocardial T1relaxation time prior to contrast enhancement (r=–0.5; p<0.0001).Conclusion. Myocardial T1 time relaxation mapping before contrast enhancement has detected that ECV in patients with HCM is much higher than in those with the intact myocardium. LV deformation in patients with HCM correlates with changes in myocardial T1 time and the magnitude of myocardial hypertrophy and to a lesser extent with focal LV fibrosis.